2018
DOI: 10.1097/md.0000000000010061
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for common cold

Abstract: Background:The common cold (CC) is the most common syndromes of infection in human beings, but there is currently no special treatment. For this reason, acupuncture is used to relieve the symptoms of the CC. Acupuncture is a traditional Chinese medicine (TCM) therapy that has been used for over 2000 years to treat various diseases. However, few studies have provided evidence for the efficacy and safety of acupuncture for the CC. This study aims to evaluate the effectiveness and safety of acupuncture on CC peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In recent times, humans spend the majority of time (almost 90%) indoors. There has been a growing concern over the health effects associated with indoor air quality since airborne diseases, including influenza [ 19 ], tuberculosis [ 20 ], the common cold [ 21 ], and legionellosis [ 22 ], exist in indoor air. Several studies have documented that humans who are exposed daily to these airborne particles can induce allergic and chronic inflammatory responses [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, humans spend the majority of time (almost 90%) indoors. There has been a growing concern over the health effects associated with indoor air quality since airborne diseases, including influenza [ 19 ], tuberculosis [ 20 ], the common cold [ 21 ], and legionellosis [ 22 ], exist in indoor air. Several studies have documented that humans who are exposed daily to these airborne particles can induce allergic and chronic inflammatory responses [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…3) The common cold is still deemed incurable and is only treated symptomatically using various medications, 1,2) such as antihistamines, analgesics, decongestants, antitussives, antipyretics, 4,5) and other beneficial drug therapies. 6,7) Several animal studies have found that vitamin C increases resistance to viral and bacterial infections, and it was hypothesized that vitamin C would have a similar effect on humans. [8][9][10] In 1970, Pauling, who had won Nobel Prizes for Chemistry (1954) and Peace (1962), claimed that vitamin C prevented the occurrence of common cold and alleviated its symptoms.…”
Section: Introductionmentioning
confidence: 99%